Comparative effectiveness and safety of direct oral anticoagulants versus warfarin among patients with recurrent venous thromboembolism - Hye‐Rim Kang; Eric A. Dietrich; Pei‐Lin Huang; Wei‐Hsuan Lo‐Ciganic; Christina E. DeRemer; Haesuk Park (Wiley, 2023)
Abstract The comparative effectiveness and safety of oral anticoagulant therapies to prevent a second recurrent venous thromboembolism (VTE) remains undetermined. We aimed to compare the benefits and harms of direct oral anticoagulant (DOAC) and warfarin therapies in preventing second recurrent VTE and major bleeding events among patients with a recurrent VTE episode following anticoagulation therapy for incident VTE. A retrospective cohort analysis of two large national insurance claims databases was conducted for patients with two episodes of VTE. Cox proportional hazards models were used after inverse probability treatment weighting to compare risks of second recurrent VTE and major bleeding events. Compared with warfarin, DOAC therapy was associated with significantly decreased risk of second recurrent VTE with no significant difference in risk of major bleeding events. Our findings suggest that, compared with warfarin, DOACs may reduce risk of second VTE recurrence among patients who have experienced one recurrence.